Mechanical Design, Analysis, and Dynamics Simulation of a Cable-Driven Wearable Flexible Exoskeleton System - Xuetong Jin; Wenqian Ding; Mathias Baumert; Yan Wei; Qinglin Li; Wei Yang; Yuqiao Yan (Technologies)
As a new development direction in exoskeleton research, wearable flexible exoskeleton systems are highly favored for their freedom of movement, flexibility, lightweight design, and comfortable wearability. These systems are gradually becoming the preferred choice for rehabilitation therapy, and enhancing physical performance. In this thesis, based on existing research in wearable flexible exoskeletons, we aim to design a lightweight wearable upper limb rehabilitation exoskeleton that meets the needs of stroke patients with a high likelihood of upper limb impairment. The system should provide sufficient flexibility for comfortable and convenient use while minimizing the weight to reduce the user’s burden during wear. Our proposed lightweight wearable flexible exoskeleton assists users in achieving rehabilitation exercises for both the shoulder (external/internal rotation) and forearm (flexion/extension) movements. The system consists of a flexible fabric section connecting the torso–shoulder–upper arm, a flexible fabric section for the forearm, and a back-mounted actuation device. The fabric sections primarily consist of elastic textile materials with a few rigid components. Emphasizing lightweight design, we strive to minimize the exoskeleton’s weight, ensuring optimal user comfort. The actuation device connects to the fabric sections via tensioned wires, driven by a motor to induce arm movement during rehabilitation exercises. To enhance safety and prevent secondary upper limb injuries due to exoskeleton malfunction, we incorporate a physical limiter retricting the exoskeleton’s range of motion. Additionally, we include tension-adjustment mechanisms and cushioning springs to improve the feasibility of this wearable flexible exoskeleton. After completing the structural design, this paper conducted a basic static and kinematic analysis of the exoskeleton system to provide theoretical support. Additionally, the feasibility and effectiveness of the exoskeleton system design were verified through dynamic simulations.